Analysis of The Influence of Digital Marketing Strategy on Repurchase Intention with Competitive Advantage and Perceived Brand Interactivity as Mediating Variables at OKI-I Okonomiyaki Shop, Malang City - Rizky Dwi Novrianto (Eduvest - Journal of Universal Studies, 2024)
This research analyzed the influence of Digital Marketing Strategy on Repurchase Intention with Competitive Advantage and Perceived Brand Interactivity as moderating variables at Kedai Oki-I Okonomiyaki, Malang City. The research method used a descriptive explanatory approach with multiple linear regression analysis, path analysis, and hypothesis testing techniques. The research population was 700 visitors with a sample of 255 respondents taken by proportional random sampling. Data were collected through questionnaires and processed using SPSS version 25. The results showed that Digital Marketing Strategy had a significant positive effect on Repurchase Intention, Competitive Advantage, and Perceived Brand Interactivity. Competitive Advantage and Perceived Brand Interactivity also had a significant positive effect on Repurchase Intention and moderated the influence of Digital Marketing Strategy on Repurchase Intention.